Antihyperuricemic Activity Of Ficus Carica Leave Extract in Mus Musculus - Andri Priyoherianto (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
ABSTRACT Ficus carica L. is one of the many plants containing flavonoid compounds. The benefits of flavonoids here are inhibiting free radicals by inhibiting enzymes responsible for the production of superoxide radicals such as xanthine oxidase. The aim of this research is to know the effect of Tin leaf extract (Ficus carica L.) on the level of uric acid mice (Mus musculus) induced by homogenate of chicken liver, quail egg yolk, and jelanta oil. Mice as many as 30 tails divided into 6 groups, each consisting of 5 tails. Group 1 as normal control, group 2 as negative control was given 1% CMC-Na, group 3, 4, and 5 were given Tin leaf extract at consecutive doses of 140 mg, 420 mg, and 820 mg / KgBB. Group 6 as positive control was given allopurinol 13 mg / KgBB. Determination of uric acid levels using the calibrated EasyTouch®GCU digital tool. The percentage decrease uric acid level at dose 140 mg / KgBB, 420mg / kgBB, and 820mg / KgBB respectively is 10.4%; 11.4%; and 39.1%. Dose 820mg / KgBB gives the biggest decrease that is equal to 39,1%, if compared with other group hence positive control group that is Allopurinol give biggest decrease 57,8%. Based on the result of analysis using cruciate wallis test with significance value <0,05 indicates that there is difference of each group.